Meteorological and ground observations in the Qinghai-Tibet Engineering Corridor - Lihui Luo (Zenodo, 2021)
The observations of meteorological factors were carried out from two permanent meteorological stations (Golmud and Wudaoliang) and one field meteorological station (Xidatan) with daily meteorological records for the period 2014-2018. Ground temperature and moisture data from the near-surface to within 270 cm in the active layer were recorded for the permafrost slope.